Analisis Strategi McD dalam Memasuki Pasar Global - Hermika Pinem; Monika Ayu Lumbantoruan; Resy Tamara; Aurora Elise Putriku; Lenti Susanna Saragih (Pusat Riset dan Inovasi Nasional, 2024)
The global market offers great growth opportunities but is also challenging for firms. This research aims to understand how companies can successfully enter and survive in the global market. The research method used is a literature study to analyze the company's business strategy. The results show that McDonald's (McD) is a successful example of entering the global market by using effective franchising and marketing strategies. The franchise strategy allows adaptation to local culture and builds a strong customer base. McD's marketing strategy emphasizes creative promotions and improved product quality.From the research conducted, it is known that a combination of effective business adaptation and marketing strategies can lead to global success in the food industry. McD is an example of how companies can succeed in a competitive global market.